Pengaruh Online Customer Review dan Online Customer Rating Terhadap Keputusan Pembelian melalui Marketplace fitur Tiktok Shop pada Aplikasi Tiktok - Hatta, Osam Moh; Wahono, Budi; Rahman, Fahrurrozi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abtract This research aims to determine the influence of Online Customer Reviews and Online Customer Ratings on purchasing decisions through the marketplace on the TikTok application with the TikTokshop feature at the Islamic University of Malang. This research was carried out by distributing questionnaires online via Google Form to students at the Islamic University of Malang who had made repeat purchases in the last 6 months. The sample was determined using a purposive sampling method. The number of respondents collected was 60, then data processing was carried out using IBM SPSS Version 29 software. The results of this research state that Online Customer Reviews and Online Customer Ratings simultaneously have a positive and significant influence on Purchasing Decisions through the TikTokshop feature marketplace in the application. Keywords : online customer reviews, online customer ratings, buying decision